THE ROLE OF PARENTAL INVOLVEMENT IN PEDAGOGY: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Parental involvement in pedagogy plays a crucial role in shaping a child's educational journey and overall development. This article examines the multifaceted impact of parental engagement on various aspects of pedagogy, including academic achievement, socio-emotional development, and lifelong learning habits. Drawing upon theoretical frameworks and empirical research, it elucidates how different forms of parental involvement, such as home-based activities, communication with educators, and participation in school events, contribute to enhancing educational outcomes. Moreover, this article highlights the importance of establishing collaborative partnerships between parents, educators, and communities to create a supportive learning environment for children. By exploring the complexities and benefits of parental involvement in pedagogy, this abstract aims to provide insights for educators, policymakers, and parents to foster effective educational practices and promote student success.